2013
DOI: 10.1097/id.0b013e3182777239
|View full text |Cite
|
Sign up to set email alerts
|

Case of Severe Bone Atrophy of the Posterior Maxilla Rehabilitated With Blocks of Equine Origin Bone

Abstract: The deantigenated equine bone was biocompatible and resorbed only minimally. This material seems to offer excellent potential for being incorporated in a procedure that increases the width of edentulous alveolar crests.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(15 citation statements)
references
References 31 publications
(24 reference statements)
2
13
0
Order By: Relevance
“…Allografts and xenografts are osteoconductive but not osteoinductive [4,5], unlike other xenograft equine-derived biomaterials. They are used successfully in several fields of oral surgery [6][7][8][9][10][11][12][13][14] and should be preferred for being resistant to prion infections (i.e., Bovine Spongiform Encephalopathies) [15,16].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Allografts and xenografts are osteoconductive but not osteoinductive [4,5], unlike other xenograft equine-derived biomaterials. They are used successfully in several fields of oral surgery [6][7][8][9][10][11][12][13][14] and should be preferred for being resistant to prion infections (i.e., Bovine Spongiform Encephalopathies) [15,16].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, nonantigenic equine bone retains type I collagen, along with a cellular matrix that contains a high amount of growth factors such IGF II, TGF-beta, IGF I, PDGF, bFGF, and BMPs [17]. Many vitro studies show the positive effects of collagen in the production of new bone [7,[18][19][20].…”
Section: Introductionmentioning
confidence: 99%
“…Equine-derived bone substitutes have shown optimal results in oral surgery and a good safety profile [ 7 , 8 , 11 , 28 – 32 ]. Unlike almost all other heterologous bone grafts, they have also demonstrated osteoinductive properties and the preservation of several growth factors which enhance osteocyte colonization and new bone development [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…It has been reported that a bone block is a reliable material for regenerative procedures with predictable long-term positive results [ 33 ]. The space maintaining characteristics of the blocks can overcome the poor three-dimensional stability of the particulate substitutes offering an adequate mechanical support to the overlying tissue [ 16 , 34 , 35 ].…”
Section: Introductionmentioning
confidence: 99%